Ethnic fragmentation and degree of urbanization strongly affect the discrimination power of Y-STR haplotypes in central Sahel. (November 2020) - Della Rocca, Chiara; Cannone, Francesco; D'Atanasio, Eugenia; Bonito, Maria; Anagnostou, Paolo; Russo, Gianluca; Barni, Filippo; Alladio, Eugenio; Destro-Bisol, Giovanni; Trombetta, Beniamino; Berti, Andrea; Cruciani, Fulvio
Highlights: 431 males from Cameroon and Chad analysed by using 27 Y-STRs and 82 Y-SNPs. Extensive haplotype sharing for males from the same ethnic group and location. Significant correlation between location census size and discrimination capacity. Genetic differentiation among neighbouring villages exceeded that among countries. Implications for the choice of the appropriate reference population database. Abstract: Y chromosome short tandem repeats (Y-STRs) are commonly used to identify male lineages for investigative and judicial purposes and could represent the only source of male-specific genetic information from unbalanced female-male mixtures. The Yfiler Plus multiplex, which includes twenty conventional and seven rapidly-mutating Y-STRs, represents the most discriminating patrilineal system commercially available to date. Over the past five years, this multiplex has been used to analyze several Eurasian populations, with a reported discrimination capacity (DC) approaching or corresponding to the highest possible value. However, despite the inclusion of rapidly mutating Y-STRs, extensive haplotype sharing was still reported for some African populations due to a number of different factors affecting the effective population size. In the present study, we analyzed 27 Y-STRs included in the Yfiler Plus multiplex and 82 Y-SNPs in central Sahel (northern Cameroon and western Chad), an African region characterized by a strong ethnic fragmentation and linguistic diversity. We evaluated the effects of population sub-structuring on genetic diversity by stratifying a sample composed of 431 males according to their ethnicity (44 different ethnic groups) and urbanization degree (four villages and four towns). Overall, we observed a low discrimination capacity (DC = 0.90), with 71 subjects (16.5 %) sharing 27 Y-STR haplotypes. Haplotype sharing was essentially limited to subjects with the same binary haplogroup, coming from the same location and belonging to the same ethnic group. Haplotype sharing was much higher in rural areas (average DC = 0.83) than urban settlements (average DC = 0.96) with a significant correlation between DC and census size (r = 0.89; p = 0.003). Notably, we found that genetic differentiation between villages from the same country ( Φ ST  = 0.14) largely exceeded that found among countries ( Φ ST  = 0.02). These findings have important implications for the choice of the appropriate reference population database to evaluate the statistical relevance of forensic Y-haplotype matches.